2017
DOI: 10.1021/acs.jpcc.7b07462
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nonlocal Response Effects on Dipole Decay Dynamics in the Weak- and Strong-Coupling Regimes

Abstract: The largest increases in spontaneous decay rates of quantum emitters can be achieved using plasmonic structures that are characterized by closely spaced metallic elements. These systems can give rise to the smallest optical cavities attainable, offering a viable solution to achieve single molecule light-matter strong-coupling. On the other hand, their optical response might be strongly affected by nonlocal and quantum effects of the metal electron gas. In this work, we analyze the impact of nonlocal effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…While this is somehow expected in the QHT case because of the extra losses due to viscosity, it is a surprising result for the TF-HT. In fact, although similar systems have already been investigated by some of the authors of this article [70], this result has not been observed before. On the contrary, Tserkezis et al [56,71] have demonstrated robustness of strong coupling against nonlocal corrections, when collective emitters are considered.…”
Section: Spheresmentioning
confidence: 51%
See 1 more Smart Citation
“…While this is somehow expected in the QHT case because of the extra losses due to viscosity, it is a surprising result for the TF-HT. In fact, although similar systems have already been investigated by some of the authors of this article [70], this result has not been observed before. On the contrary, Tserkezis et al [56,71] have demonstrated robustness of strong coupling against nonlocal corrections, when collective emitters are considered.…”
Section: Spheresmentioning
confidence: 51%
“…Metallic structures that are characterized by few-nanometer or even sub-nanometer inter-particle distances achieve the largest optical field confinement [25,29] and smallest optical cavity volumes, and are ideal candidates for achieving single-molecule room temperature strong coupling [56,62,[70][71][72]. We consider dimers of Drude-like Na spheres of radius R and gap size g = 2d.…”
Section: Sphere Dimersmentioning
confidence: 99%
“…Note that for gaps smaller than 5 nm, the nonlocal response of the metal may become pronounced, whereas our calculations of the coupling strength are based on the local model. This may have an unfavorable effect on the coupling strength as recent theoretical efforts suggest [70].…”
Section: B Comparative Study Of the Nanoantenna Geometrymentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, when the size of the particles or junctions is only a few nanometers or smaller, the quantum nature of electrons emerges, activating quantum tunneling effects across subnanometer interparticle gaps. 19,20,[30][31][32][32][33][34][35][36][37][38][39][40][41][42][43][44] Tunnelling effects are not considered in classical models, so that quantum corrected approaches need to be applied. 37,41 The theoretical study of the atomic-scale features in nanojunctions is still an almost unexplored field, because most phenomenological classical models do not address quantum effects.…”
Section: Introductionmentioning
confidence: 99%